2016
DOI: 10.1016/j.bjm.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces lunalinharesii 235 prevents the formation of a sulfate-reducing bacterial biofilm

Abstract: Streptomyces lunalinharesii strain 235 produces an antimicrobial substance that is active against sulfate reducing bacteria, the major bacterial group responsible for biofilm formation and biocorrosion in petroleum reservoirs. The use of this antimicrobial substance for sulfate reducing bacteria control is therefore a promising alternative to chemical biocides. In this study the antimicrobial substance did not interfere with the biofilm stability, but the sulfate reducing bacteria biofilm formation was six-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Strains from the genus Desulfovibrio are established sulphide producers and thus represent a major concern for the oil and gas industry 62 , 63 . What stands out immediately from the results is the importance of the Desulfovibrio 64 , 65 . Desulfovibrio are known to cause corrosion, hydrogen sulphide production, souring and biofouling within the operational plants 71 , 72 .…”
Section: Resultsmentioning
confidence: 78%
“…Strains from the genus Desulfovibrio are established sulphide producers and thus represent a major concern for the oil and gas industry 62 , 63 . What stands out immediately from the results is the importance of the Desulfovibrio 64 , 65 . Desulfovibrio are known to cause corrosion, hydrogen sulphide production, souring and biofouling within the operational plants 71 , 72 .…”
Section: Resultsmentioning
confidence: 78%
“…They investigated P. aeruginosa mutants, defective in rhamnolipids production, to determine the biochemical basis of SRB biofilm dispersal and concluded that rhamnolipids play a role in the dispersal of SRB biofilm (Wood et al, 2018). In addition, antimicrobial substances (AMS) produced by Streptomyces lunalinharesii strain 235 have shown to be effective against D. alaskensis NCIMB 13491 biofilm on carbon steel surfaces (Pacheco da Rosa et al, 2013;Rosa et al, 2016). The ability of D. alaskensis to form biofilm was sixfold less in the carbon steel coupons treated with AMS (0.05 g protein/ml) than the non-treated ones (Rosa et al, 2016).…”
Section: Biological Methods Of Biofilm/microbiologically Influenced Corrosion Control and Inhibitionmentioning
confidence: 99%
“…This happens because a limited number of dominant genera are responsible for the Order level diversity. What stands out immediately is the importance of the Desulfovibrio sequences 40,54 . Desulfovibrio impact negatively causing corrosion, hydrogen production, souring and biofouling caused by bio lm formation within the operational plants.…”
Section: Inmentioning
confidence: 99%